Turnaround Strategy Of Pt Indofarma Tbk - Maria Prisila Paru; Popy Rufaidah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
PT Indofarma Tbk experienced a decline in financial performance from 2016 to 2022 leading to corporate strategy implementation. This study aims to analyze the suitability of the strategy implemented by PT Indofarma to the theory of corporate alternative strategy. This study involved a case study method utilizing annual reports and financial statement data. BCG Matrix was applied as a portfolio analysis tool. PT Indofarma Tbk was identified in the BCG matrix in a low growth and market share quadrant. The strategy implemented by PT Indofarma to recover the company’s performance was identified as a turnaround strategy which aligns with the recommended strategy for a company that experienced low growth and low market share in the BCG matrix. This study concluded that the implementation of the turnaround strategy at PT Indofarma Tbk aligns with the recommendations by researchers for effective turnaround strategy implementation